2020
DOI: 10.1016/j.celrep.2020.108416
|View full text |Cite
|
Sign up to set email alerts
|

DNMT3A Haploinsufficiency Results in Behavioral Deficits and Global Epigenomic Dysregulation Shared across Neurodevelopmental Disorders

Abstract: Highlights d Disease-associated DNMT3A mutations disrupt deposition of neuronal DNA methylation d Heterozygous DNMT3A mutant mice show disease-relevant growth and behavior phenotypes d Heterozygous DNMT3A mutation globally reduces non-CG DNA methylation in the brain d RNA and epigenomic changes in DNMT3A mutants overlap MeCP2 disorder and autism models

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(97 citation statements)
references
References 100 publications
6
89
2
Order By: Relevance
“…SCZ-like symptoms (including auditory hallucinations) were also recently reported in three patients with novel, predicted deleterious variants in the DNMT3A-coding sequence [255]. Mice hemizygous for Dnmt3a also exhibit behavioral deficits, including reduced exploration and increased anxiety-like behaviors [256]. However, no deficits in pre-pulse inhibition (PPI), a common deficit in patients with SCZ, were observed in these mice.…”
Section: Shared Roles Of Mir-29 and Mir-132-3p: Cortical Ocular Dominance Plasticity And Dnmt3amentioning
confidence: 81%
“…SCZ-like symptoms (including auditory hallucinations) were also recently reported in three patients with novel, predicted deleterious variants in the DNMT3A-coding sequence [255]. Mice hemizygous for Dnmt3a also exhibit behavioral deficits, including reduced exploration and increased anxiety-like behaviors [256]. However, no deficits in pre-pulse inhibition (PPI), a common deficit in patients with SCZ, were observed in these mice.…”
Section: Shared Roles Of Mir-29 and Mir-132-3p: Cortical Ocular Dominance Plasticity And Dnmt3amentioning
confidence: 81%
“…The lack of differential expression levels of Pgc1α as a function of brain region was further confirmed by RT-PCR in an independent cohort of males, in which we probed the levels of the reference gene and the SSR-SINE-exon 2 isoform (Fig S4C). Analysis of publicly available RNA-seq data from male and female brain (Christian et al, 2020) showed that levels of the reference or SSR-SINE-exon 2 isoforms were not different based on sex (Fig S4D). Thus, the loss of the protein derived from the SSR-SINE-exon 2 isoform leads to a sexually dimorphic cerebellar transcriptional profile that cannot to be simply explained by differences in its expression in male or female brains.…”
Section: Sine-mutant Female Mice Exhibit Increased Neurotransmitterassociated Gene Expression In the Cerebellummentioning
confidence: 99%
“…In mature neurons, DNMTs expression was maintained at a high level, and DNMT3A knockout induced the synaptic alteration and learning de cit, which directly in uenced learning and memory behavior, thus DNMT3A in the postmitotic neuron was a key regulator in memory formation [71]. DNMT3A loss caused widespread transcriptional alterations and severe impairment of neuronal function [72], and DNMT3A Haploinsu ciency in the brain led to neurodevelopmental disorders involved in growth and behavioral alterations [73]. Recently, it has been revealed that hypoxic preconditioning exerted anti-hypoxic neuroprotection and maintained HT22 cell proliferation and viability through downregulation of the expression levels of DNMT3A and DNMT3B mRNA and protein [74].…”
Section: Discussionmentioning
confidence: 99%